The Success of the Management of the Remote Area Mobilization Teacher Program in Improving the Quality of Education in the Mappi District - Marito Br Tamba, Juni Sihol; Munir, Munir; Hartini, Nani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aims to analyze the success of managing the teacher mobilization program in remote areas in improving the quality of education in Mappi District. The research method uses a descriptive qualitative approach. The data were collected using interviews, documentation studies, and observation. Data validation was carried out using technical triangulation and source triangulation. The data analysis technique used refers to the Miles and Hurben model, which includes four stages, namely: (1) data collection, (2) data reduction, (3) data display, and (4) conclusion. The results of this study are that the implementation of the teacher mobilization program in remote areas based on research has gone quite well; in this case, the GPDT qualification target is still not by the initial plan based on the report on recruitment activities made by the UGM Papua Task Force; there are still many teachers who are placed not by the qualifications of the majors of teacher expertise. It was concluded that the program's success in improving the quality of education was effective in producing quality graduates in quantity, which increased every year, and the HDI and GPA/IPM scores increased every year from 2016 to 2021.